Guide :

What is the answer to 105.6 l/h = l/min

How do you get the answer to this problem because I'm not understanding

Research, Knowledge and Information :


105.6 L/h= L/min? - Weknowtheanswer - #1 Questions & Answers ...


105.6 L/h= L/min? Find answers now! ... 105.6 L /h = L / min Q8: The table shows the total distance traveled by a car driving at a constant rate ...
Read More At : www.weknowtheanswer.com...

105.6 L/h = ___ L/min? - Brainly.com


105.6 L/h = ___ L/min? 1. Ask for details ; Follow; Report; by xxrockstarxx 01/22/2015. Log in to add a comment ... Answers come with explanations, so that you can learn.
Read More At : brainly.com...

105.6 L/h = ___ L/min? - Brainly.com


105.6 L/h = 1.76 L/min :)))) i hope this be helpful have a nice day Comments (3) Report; 0. Thanks. 2. ... Answers come with explanations, so that you can learn.
Read More At : brainly.com...

Convert L/min to L/h | Liter per minute to Liters per hour


Diferent flow rate units conversion from Liter per minute to Liters per hour. Between L/min and L/h measurements conversion chart page. ... L/h ANSWER: 1 L/min = 60 ...
Read More At : www.traditionaloven.com...

L/h to L/min Converter, Chart -- EndMemo


Flow unit conversion between liter/hour and liter/minute, liter/minute to liter/hour conversion in batch, L/h L/min conversion chart. ... L/h↔mL/s 1 mL/s = 3.6 L/h
Read More At : www.endmemo.com...

1) 45 mi/h= _____ ft/s 2) 26 cm/s=_____ m/min ... - OpenStudy


... 26 cm/s=_____ m/min 3) 24 mi/h=_____ ft/s 4) 105.6 L/h=_____ L/[email protected] . First convert your miles into feet, a ... We 've verified this expert answer for you, ...
Read More At : openstudy.com...

L/min to L/s Converter, Chart -- EndMemo


Flow unit conversion between liter/minute and liter/second, liter/second to liter/minute conversion in batch, L/min L/s conversion chart. ENDMEMO.
Read More At : www.endmemo.com...

Suggested Questions And Answer :


3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer how do you solve it and what are the answers ? 1)  3x + 6y – 6z = 9 2)  2x – 5y + 4z = 6 3)  -x +16y + 14z = -3 The first objective is to eliminate z so we can solve for x and y. It's a multi-step process, so follow along. Multiply equation one by 4. 4 * (3x + 6y – 6z) = 9 * 4 4)  12x + 24y - 24z = 36 Multiply equation 2 by 6. 6 * (2x – 5y + 4z) = 6 * 6 5)  12x - 30y + 24z = 36 Now, we have two equations with a "24z" term. Add the equations and the z drops out. Add equation five to equation four.    12x + 24y - 24z = 36 +(12x - 30y + 24z = 36) ----------------------------------    24x -  6y           = 72 6)  24x - 6y = 72 The same process applies to equations two and three. Multiply equation two by 7 this time. 7 * (2x – 5y + 4z) = 6 * 7 7)  14x - 35y + 28z = 42 Multiply equation three by 2. 2 * (-x + 16y + 14z) = -3 * 2 8)  -2x + 32y + 28z = -6 Subtract equation eight from equation seven.   14x - 35y + 28z = 42 -(-2x + 32y + 28z = -6) ---------------------------------   16x - 67y          = 48 9)  16x - 67y = 48 Looking at equations six and nine, it would be simpler to eliminate the x. The multipliers are smaller. Multiply equation six by 2. 2 * (24x - 6y) = 72 * 2 10)  48x - 12y = 144 Multiply equation nine by 3. 3 * (16x - 67y) = 48 * 3 11)  48x - 201y = 144 Subtract equation eleven from equation 10.   48x -   12y = 144 -(48x - 201y = 144) ---------------------------          189y  =   0 189y = 0 y = 0  <<<<<<<<<<<<<<<<<<<<<<<<<<<<<< Substitute that value into equations six and nine to solve for x and verify. Six: 24x - 6y = 72 24x - 6(0) = 72 24x - 0 = 72 24x = 72 x = 3  <<<<<<<<<<<<<<<<<<<<<<<<<<<<<< Nine: 16x - 67y = 48 16x - 67(0) = 48 16x - 0 = 48 16x = 48 x = 3    same answer for x To solve for z,substitute the x and y values into the three original equations. One: 3x + 6y – 6z = 9 3(3) + 6(0) – 6z = 9 9 + 0 - 6z = 9 9 - 6z = 9 -6z = 9 - 9 -6z = 0 z = 0  <<<<<<<<<<<<<<<<<<<<<<<<<<<<<< Two: 2x – 5y + 4z = 6 2(3) – 5(0) + 4z = 6 6 - 0 + 4z = 6 6 + 4z = 6 4z = 6 - 6 4z = 0 z = 0     same answer Three: -x +16y + 14z = -3 -(3) +16(0) + 14z = -3 -3 + 0 + 14z = -3 -3 + 14z = -3 14z = -3 + 3 14z = 0 z = 0     once again, same answer x = 3, y = 0, z = 0
Read More: ...

What is the answer to 4x-2y=0 when 4x+y=0?

What is the answer to 4x-2y=0 when 4x+y=0? This problem is for using addition to solve a system if that makes any sense. Like if a problem was 3x-2y=5 when 4x+2y=-16, the answer would be -3,-2. 4x - 2y = 0  and   4x+y=0   -1 * (4x + y) = -1 * 0   -4x -3 = 0 -4x - y = 0 ---------------      -3y = 0        y = 0 4x - 2y = 0 4x - 2(0) = 0 4x - 0 = 0 4x = 0 x = 0 The (x, y) pair is (0,0), the origin. This is obvious since the y-intercept for both equations is zero. 4x - 2y = 0 -2y = -4x + 0 y = 2x + 0   set x to zero, y is zero 4x + y = 0 y = -4x + 0   set x to zero, y is zero
Read More: ...

Whats the x and y intercepts of y=5x-2 and -2/3x=9?

The x-intercept (where y = 0) of y = 5x - 2 0 = 5x - 2 2 = 5x x = 5/2 Answer:  (5/2,0) . The y-intercept (where x = 0) of y = 5x - 2 y = 5(0) - 2 y = -2 Answer:  (0,-2) . The x-intercept of (-2/3)x = 9 (-2/3)x = 9 x = 9 * -3/2 x = -27/2 Answer:  (-27/2,0) . The y-intercept of (-2/3)x = 9 This is a vertical line, so it never crosses the y-axis. See what happens if we ask the question "what happens if x=0 ?" (-2/3)0 = 9 0 = 9 Since it is never true that 0 = 9, that means x can never be 0, which means there is no y-intercept. Answer:  Does not exist.
Read More: ...

Determine the first derivative (dy/dx) : y= f(x)=x^3-3x+2

Please note that the title to this question has y=f(x)=x^3-3x+2 but the text of the question has y=f(x)=3x^3-3x+2, which is the equation I have used in my answer. (a) 1. f'(x)=dy/dx=9x^2-3 using the rules of differentiation 2. f"(x)=18x (gives the nature of any turning point) 3 and 4: f'=0 at a turning point, so 9x^2=3 and x^2=1/3 so x=±1/√3 or ±√3/3 in rational form. When x>0 f">0 and when x<0 f"<0. This means that x=√3/3 is a minimum and x=-√/3 is a maximum.  5. There is no point of inflexion. 6. The graph is shown below. The intercepts are y=2 and the root(s) of 3x^3-3x+2=0. They only point where the curve intercepts the x axis is about x=-1.24. If f(x)=x^3-3x+2 was the intended equation, the graph will look similar (not the same) but all the answers will not fit. Nevertheless I think you can work out the answers for yourself given the general idea of how to do so in this solution. The major difference is that x^3-3x+2 factorises: (x+2)(x-1)^2 with roots x=-2 and x=1 (x intercepts, so the curve cuts or touches the x axis twice). Also the max and min are at x=±1 (max at x=-1 and min at x=1). The graph below of x^3-3x+2 clearly shows the intercepts with the curve just touching (not intercepting) the x axis at x=1, while x=-1 is a clear intercept. The turning points are (-1,4) (max) and (1,0) (min). If you would like a full solution to this, add a comment to this answer and I will answer using a comment reply.
Read More: ...

what is the answer to ... -2x+y=0 -3x-2y=-35

1) -2x + y = 0 2) -3x - 2y = -35 We can eliminate y; multiply equation 1 by 2. 2 * (-2x + y) = 0 * 2 3) -4x + 2y = 0 Add equation 2 to equation 3.    -4x + 2y =    0 +(-3x - 2y = -35) ----------------------    -7x        = -35 -7x = -35 -7x/-7 = -35/-7 x = 5 With that, we can use equation 1 to solve for y. -2x + y = 0 -2(5) + y = 0 -10 + y = 0 -10 + y + 10 = 0 + 10 y = 10 Use equation 2 to check the answers. -3x - 2y = -35 -3(5) - 2(10) = -35 -15 - 20 = -35 -35 = -35 Answer: x = 5, y = 10 Problem statement: what is the answer to ... -2x+y=0 -3x-2y=-35 it has to do with "solving systems of equations:elimination method  
Read More: ...

what is the answer to 4y=12y squared

Problem: what is the answer to 4y=12y squared I dn't know to work this problem 4y = 12y^2 12y^2 = 4y 12y^2 - 4y = 0 12y^2 - 4y + 0 = 0    included + 0 to show c in the quadratic formula       -b ± √(b² - 4*a*c) y = --------------------               2a       -(-4) ± √((-4)² - 4*12*0) y = -------------------------------                 2(12)       4 ± √(16² - 0) y = -----------------             24         4 ± √(16²) y = -----------------             24        4 ± 4 y = ---------          24        4 + 4                        4 - 4 y = ---------     and   y = ---------          24                           24          8                             0 y = ---------     and   y = ---------         24                           24 y = 1/3           and   y = 0 Check both values. 4y = 12y^2 4(1/3) = 12(1/3)^2 4/3 = 12(1/9) 4/3 = 4(1/3) 4/3 = 4/3 4y = 12y^2 4(0) = 12(0)^2 0 = 12(0) 0 = 0 Answer: y = 1/3,  y = 0  
Read More: ...

Volume of a solid

Because the answer is long, I answered in two stages so as not to lose any text which sometimes happens when there's a network glitch. Sorry if this caused you confusion. Here's my original complete answer: 1. The integral can be considered to be the sum of the volumes of discs parallel to the x axis. The radius of each disc is 4-x because the widest disc has radius 4, when x=0, reducing to zero as x approaches 4. For example, at x=1 the radius is 3. The thickness of each disc is dy so the integral is (pi)S((4-x)^2dy, where S denotes integral. y=sqrt(x) so y^2=x and the integral is (pi)S((4-y^2)^2dy) between limits for y of 0 to 2, written [0,2]. The integral in y becomes: (pi)S[0,2]((4-y^2)^2dy)=(pi)S[0,2]((16-8y^2+y^4)dy)= (pi)(16y-8y^3/3+y^5/5)[0,2]= (pi)(32-64/3+32/5)=256(pi)/15=53.62 cu units approx. 2. This time the discs are vertical with thickness dx and radius 2-y, where x goes from 0 to 4 (y ranges from 0 to 2). The integral is (pi)S[0,4]((2-y)^2dx)= (pi)S[0,4]((4-4y+y^2)dx)= (pi)S[0,4]((4-4sqrt(x)+x)dx)= (pi)(4x-2x^-(1/2)+x^2/2)[0,4]= (pi)(16-1+8)=23(pi)=72.26 cu units approx.
Read More: ...

what is 1/2 minus 1/2

x-x=0, & that inklude 1/2 - 1/2=0 even tho it is tru 0=0/weisdfje or perhaps zeresiot*0 wi du yu want that as yer anser?
Read More: ...

If a ball is thrown straight upwards with a velocity of 80 ft/s...

s = 80t - 16t^2 One way to do it: The ball starts at a height of 0 and ends at a height of 0.  Find when that happens. 0 = 80t - 16t^2 0 = t(80 - 16t) 80 - 16t = 0 80 = 16t t = 5 The ball will return to the ground at t = 5 seconds.  The maximum height will happen halfway between the start at t = 0 and the end at t = 5. Answer:  2.5 seconds. . Another way: s = 80t - 16t^2 is an upside-down parabola.  The maximum height happens at the top of the parabola, where the parabola is flat (slope = 0, first derivative = 0). s ' = 80 - 32t 0 = 80 - 32t 32t = 80 t = 2.5 Answer:  2.5 seconds.
Read More: ...

seven times a two digit number

Short answer:  The two digit number is 36. Long answer: 7 * x1x2 = 4 * x2x1 "If the difference between the number is 3. . ." Last digits: x2: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9 7*x2:  0, 7, 4, 1, 8, 5, 2, 9, 6, 1 x1:  0, 1, 2, 3, 4, 5, 6, 7, 8, 9 4*x1:  0, 4, 8, 2, 6, 0, 4, 8, 2, 6 The only way this works is when these last digits for 7*x2 and 4*x1 are the same.  That means the 7*x2 line can only be: 7*x2:  0, 4, 8, 2, 6 Which means the possible values for x2 are: x2:  0, 2, 4, 6, 8 Now let's look at x1.  Right now the possible values for x1 are: x1:  0, 1, 2, 3, 4, 5, 6, 7, 8, 9 But we have to end up with a choice from x1 and x2 having a difference of 3 (odd number).  There is no way to get an odd number by subtracting an even number from an even number.  That means x1 has to be odd.  Our possible values for x1 are now: x1:  1, 3, 5, 7, 9 And our possible values for x2 are: x2:  0, 2, 4, 6, 8 The possible combinations for x1x2 and x2x1 are: 10, 01 12, 21 14, 41 16, 61 18, 81 30, 03 32, 23 34, 43 36, 63 38, 83 50, 05 52, 25 54, 45 56, 65 58, 85 70, 07 72, 27 74, 47 76, 67 78, 87 90, 09 92, 29 94, 49 96, 69 98, 89 We want 7*x1x2 = 4*x2x1, so we can do 7 * the first column and 4 * the second column: 70, 4 84, 84 98, 164 112, 244 126, 324 210, 12 224, 92 238, 172 252, 252 266, 332 350, 20 364, 100 378, 180 392, 260 406, 340 490, 28 504, 108 518, 188 532, 268 546, 348 630, 36 644, 116 658, 196 672, 276 686, 356 But since we want 7*x1x2 to equal 4*x2x1, that list reduces to: 84, 84 252, 252 The corresponding x1 and x2 values are: 12, 21 36, 63 But the difference between x1 and x2 is 3, so we can't use x1 = 1, x2=2.  We have to use x1 = 3, x2 = 6. Answer:  The two digit number is 36. Check:  7 * 36 = 4 * 63 252 = 252 good. 6 - 3 = 3 good.
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.math-problems-solved.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1335 seconds